Impact of knowledge management, knowledge sharing, and mental accounting on farmer performance in Sasi culture in Maluku Islands, Indonesia - Tri Handayani Amaliah (Knowledge & Performance Management)
The welfare of farmers and agricultural productivity are significantly influenced by challenges in business and financial management. This study investigates how knowledge management, knowledge sharing, and mental accounting impact farmer performance within the unique context of Sasi culture in Maluku Islands, Indonesia. Knowledge management provides farmers with the tools to acquire, utilize, and apply agricultural insights, while mental accounting shapes their financial decision-making and resource allocation. Using a mixed-method approach that combines WarpPLS and ethnomethodology, data were gathered through questionnaires distributed to 65 respondents and in-depth interviews with selected participants. The analysis revealed that knowledge management significantly impacts farmer performance with a path coefficient of 0.717 (p < 0.001), while mental accounting also has a positive effect with a coefficient of 0.164 (p = 0.050). However, knowledge sharing did not significantly affect performance (coefficient = 0.372, p = 0.382). The results suggest that Sasi culture, deeply rooted in local wisdom, helps integrate knowledge management and mental accounting to improve farmer welfare and agricultural income. Despite the ineffectiveness of formal knowledge sharing, the cultural practice of Sasi inherently promotes the sharing of knowledge within the community, enhancing the overall management of agricultural practices. This study emphasizes the role of local wisdom in creating sustainable agricultural practices and highlights the potential of Sasi culture to synergize modern knowledge management with traditional financial behaviors.